1981OThe m(6)A methyltransferase METTL3 promotes gastric cancer progression through facilitating primary microRNA maturation. (1st October 2019) - Sun, Y; Li, S; Yu, W; Zhao, Z; Gao, J; Chen, C; Wei, M; Liu, L
Abstract: Background: Gastric cancer is an aggressive disease that has substantial impacts on global health. N6-Methyladenosine (m6A) is an epigenetic modification on RNA that plays an important role in cancer progression. However, the biological roles of m6A and its regulators, such as METTL3, in gastric cancer, are unknown. The regulation of primary miRNA maturation by METTL3 in cancers is also unclear. Methods: Levels of m(6)A and METTL3 were measured in paired clinical tissues in gastric cancer. The functions of METTL3 were determined by in vitro and in vivo studies. The RNA targets of METTL3 were screened by correlation studies in TCGA and confirmed in our cohorts. The METTL3-mediated primary miRNA-17-92 processing was verified by PCR and RNA-immunoprecipitation. The mTOR pathway was further studied as the downstream targets of miR-17-92 cluster by immunoblot and rescue study. Influences of METTL3 on the efficacy of Everolimus were tested in cell and animal models. Results: The m6A level was upregulated in gastric cancer and prominently regulated by METTL3. Clinically, overexpression of METTL3 indicated poor prognosis and adverse pathological features. In cell and animal models, METTL3 promoted tumor growth and metastasis. Among the top seven METTL3-correlated miRNAs, six were derived from the primary miRNA pri-miR-17-92. METTL3 promoted m6A modification of pri-miR-17-92 on the A879 site, recruitment of DGCR8, and the subsequent processing into mature miRNAs. Pri-miR-17-92-derived miRNAs inhibited activation of the mTOR pathway by targeting PTEN and TMEM127. Forced expression of these miRNAs counteracted the anti-tumor and anti-mTOR effects by METTL3 knockout. In addition, METTL3 increased the sensitivity of gastric cancer to Everolimus. Conclusions: The METTL3-mediated m6A modification on pri-miR-17-92 promotes gastric cancer progression through mTOR activation. The mechanism and function of m6A methylation modification of long non-coding RNA by METTL3 in gastric cancer was reported for the first time, which offers a novel point of view on the onco-regulating role of METTL3 in cancers and may provide a new therapeutic target for GC treatment. Legal entity responsible for the study: The authors. Funding: National Natural Science Foundation of China (81172487 to Lian Liu and 81500092 to Song Li), Natural Science Foundation of Shandong Province, China (ZR201702180008 to Lian Liu). Disclosure: All authors have declared no conflicts of interest.